The Building of Economics at Adelaide (2009)
A century of activity for an institution is a milestone too significant to go unacknowledged. Even though the resources needed to write a full historical account of the first century of economics at the University of Adelaide were not available, it was decided to at least collate available information on the people who have been involved and the teaching and research programs developed since the first undergraduate subject in Economics was offered in 1901 – not least so as to provide some historical context for the 2002 External Review of the School of Economics. Since the previous External Review was fourteen years earlier, and because the pace of change has been far greater since the late 1980s than earlier in the century, more attention is given to that period than a balanced history would warrant. Descriptions of the many and varied contributions of the 100 or so faculty members employed over the century is not possible, but brief 12–line biographies are provided in Appendix 1 for the 40 per cent of those lecturers who became full Professors at Adelaide or elsewhere.